Free Electron Density Gradients Enhanced Biosensor for Ultrasensitive and Accurate Affinity Assessment of the Immunotherapy Drugs - Youqian Chen; Hongli Fan; Rui Li; Huazhi Zhang; Rui Zhou; Gang L. Liu; Chunmeng Sun; Liping Huang (Advanced Science)
Abstract Accurate affinity assessments play an important role in drug discovery, screening, and efficacy evaluation. Label‐free affinity biosensors are recognized as a dependable and standard technology for addressing this challenge. This study constructs a free electron density gradient‐enhanced meta‐surface plasmon resonance (FED‐MSPR) biosensor through a finite‐difference time‐domain simulation model, the biosensor demonstrates superior detection performance in accurately determining affinity and kinetic rate constants. By controlling the dielectric properties of the metal on the surface of the nanocup arrays, the plasmon resonance effects are easily tuned without changing the nanostructure design. Compared with the single‐layer gold chip, the triple‐layer FED‐MSPR chip demonstrated a four‐fold improvement in resolution at the optimal resonance peak. Additionally, the sensitivity and figure of merit (FOM) of the multi‐layer chip increased by 3.5 and 7.99 times, respectively. Following modification with high‐ and low‐staggered carboxylation, the noise‐signal ratio and baseline stability of the real‐time kinetic curves based on these chips are significantly enhanced. The developed carboxylation FED‐MSPR platform is successfully used to perform affinity assays for Adalimumab and TNF‐α protein, resulting in favorable dynamic curves. These findings validate the proposed FED‐MSPR biosensor platform as cost‐effective, rapid, sensitive, and label‐free, facilitating real‐time quality control in drug development.